Investigating the variability in pressure–volume relationships during hemorrhage and aortic occlusion - Mobin, Fahim Usshihab; Renaldo, Antonio C.; Carrasco Perez, Enrique; Jordan, James E.; Neff, Lucas P.; Williams, Timothy K.; Johnson, M. Austin; Rahbar, Elaheh (Frontiers in Cardiovascular Medicine, 2023)
Introduction The pressure–volume (P-V) relationships of the left ventricle are the classical benchmark for studying cardiac mechanics and pumping function. Perturbations in the P-V relationship (or P-V loop) can be informative and guide the management of heart failure, hypovolemia, and aortic occlusion. Traditionally, P-V loop analyses have been limited to a single-beat P-V loop or an average of consecutive P-V loops (e.g., 10 cardiac cycles). While there are several algorithms to obtain single-beat estimations of the end-systolic and end-diastolic pressure–volume relations (i.e., ESPVR and EDPVR, respectively), there remains a need to better evaluate the variations in P-V relationships longitudinally over time. This is particularly important when studying acute and transient hemodynamic and cardiac events, such as active hemorrhage or aortic occlusion. In this study, we aim to investigate the variability in P-V relationships during hemorrhagic shock and aortic occlusion, by leveraging on a previously published porcine hemorrhage model. Methods Briefly, swine were instrumented with a P-V catheter in the left ventricle of the heart and underwent a 25% total blood volume hemorrhage over 30 min, followed by either Zone 1 complete aortic occlusion (i.e., REBOA), Zone 1 endovascular variable aortic control (EVAC), or no occlusion as a control, for 45 min. Preload-independent metrics of cardiac performance were obtained at predetermined time points by performing inferior vena cava occlusion during a ventilatory pause. Continuous P-V loop data and other hemodynamic flow and pressure measurements were collected in real-time using a multi-channel data acquisition system. Results We developed a custom algorithm to quantify the time-dependent variance in both load-dependent and independent cardiac parameters from each P-V loop. As expected, all pigs displayed a significant decrease in the end-systolic pressures and volumes (i.e., ESP, ESV) after hemorrhage. The variability in response to hemorrhage was consistent across all three groups. However, upon introduction of REBOA, we observed significantly high levels of variability in both load-dependent and independent cardiac metrics such as ESP, ESV, and the slope of ESPVR (Ees). For instance, pigs receiving REBOA experienced a 342% increase in ESP from hemorrhage, while pigs receiving EVAC experienced only a 188% increase. The level of variability within the EVAC group was consistently less than that of the REBOA group, which suggests that the EVAC group may be more supportive of maintaining healthier cardiac performance than complete occlusion with REBOA. Discussion In conclusion, we successfully developed a novel algorithm to reliably quantify the single-beat and longitudinal P-V relations during hemorrhage and aortic occlusion. As expected, hemorrhage resulted in smaller P-V loops, reflective of decreased preload and afterload conditions; however, the cardiac output and heart rate were preserved. The use of REBOA and EVAC for 44 min resulted in the restoration of baseline afterload and preload conditions, but often REBOA exceeded baseline pressure conditions to an alarming level. The level of variability in response to REBOA was significant and could be potentially associated to cardiac injury. By quantifying each P-V loop, we were able to capture the variability in all P-V loops, including those that were irregular in shape and believe that this can help us identify critical time points associated with declining cardiac performance during hemorrhage and REBOA use.